IMPACT ON USE OF ANTIMICROBIAL PRESCRIBING ORDER FORM IN ICU DAILY PRACTICE IN ADJUSTMENT OF ANTIMICROBIAL PRESCRIBING AND IN ENHANCEMENT OF PATIENTS CLINICAL OUTCOMES - AMAL K. HUSSEIN,; MOHAMED M. IBRAHIM,; TAREK F. TAMMAM,; HATEM A. SARHAN,; GAMAL F. GAD, (International Journal of Pharma and Bio Sciences, 2017)
The aim of all workers in the medical field is saving the patients’ lives wherefore; most of physicians when their patients get infections, they start broad spectrum antibiotic immediately to save them from death by infection and sepsis. The overuse of broad spectrum antibiotics induces new strains of microorganisms which make antibiotic resistance nowadays. In present study, we investigated the impact of use antimicrobial prescribing form to help us in adjustment of antibiotic prescribing manner and to enhance patients’ clinical outcomes. The study was implemented in adult ICU which has medical and surgical beds in general hospital. It is retrospective study which compared the results of using this form within two years after January 2014 with the results of not using this form within two years before January 2014. The results indicated that there was a significant adjustment in antibiotic consumptions between different antibiotic molecules and a significant enhancement in patients’ clinical outcomes like mortality, ICU stay infection time and a non-significant decreasing in cost.